MANDARIN LEARNING STRATEGY IN HIGHER EDUCATION TO ACHIEVE THE NEW HSK STANDARD AT LEVEL 3 - Thamrin, Lily (Journal of Education Research and Evaluation, 2021)
This study aimed to see the language learning strategies used by college students in learning Mandarin as a foreign language to achieve the New HSK (Hanyu Shuiping Kaoshi)standard at Level 3, especially regarding what strategies students used in the learning. The research was a qualitative method with a descriptive case study method involving thirty (30) students of the Mandarin Education Study Program at Faculty of Teacher Training and Education at a state university in West Kalimantan. They were students who have studied for one year or two semesters. The results showed that students were aware of the importance of using language learning strategies to master Mandarin as a foreign language, with internal and external factors that support students to learn Mandarin actively. Based on the research results obtained, two strategies often used by the students were direct learning strategies consisting of memory, cognitive, and compensation, and indirect strategies consisting of meta-cognitive, affective, and social. After the students implemented the learning strategy, students' vocabulary mastery for New HSK at level 3 increased by 67%. The most often learning strategy used by the students in learning Mandarin was the meta-cognitive strategy of 90.9% and the cognitive strategy of 66.7%. The percentage of students who have never done memory strategies was only 9,12%, while for social strategies and affective strategies was 3%.